Guideline-directed medical therapy in heart failure patients with reduced ejection fraction in Palestine: Retrospective clinical audit study - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Moyad Shahwan; Sa'ed H. Zyoud; Maimona Jairoun (Elsevier, 2024)
Objectives: To assess the characteristics of patients with heart failure with reduced ejection fraction (HFrEF) and heart failure with mid-range ejection fraction (HFmrEF), as well as the current application of guideline-directed medical therapy (GDMT) in Palestine. Methods: This retrospective cohort study involved a population of heart failure (HF) patients who visited cardiology clinics at An-Najah National University Hospital and the National Hospital, Palestine. The primary outcome measures of interest were the proportions of patients prescribed guideline-based cardiovascular medications (GBCMs), such as angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin II receptor blockers (ARBs), β-blockers, and mineralocorticoid receptor antagonists (MRAs), and the corresponding optimized doses at ≥ 50 % of targets and the reasons underlying the non-prescription of GDMT. Results: A total of 70.5%, 56.6%, and 88.6% of patients were on ACEIs/ARBs, MRAs, and β-blockers, respectively. Of all patients, 38.7% were on the triple GDMT regimen. Conclusion: Less than half the patients received the triple combination treatment. Age, diabetes mellitus, chronic renal disease, and admission to the hospital for HF all had significant independent relationships with the reduced utilization and inadequate dosage of GDMT.